Impact of a paediatric cardiac rehabilitation programme upon patient quality of life. (7th May 2021) - Kroll, Kristin H.; Kovach, Joshua R.; Ginde, Salil; Jacobsen, Roni M.; Danduran, Michael; Foster, Andrea; Brosig, Cheryl L.
Abstract: Introduction: Cardiac rehabilitation programmes for paediatric patients with congenital heart disease (CHD) have been shown to promote emotional and physical health without any associated adverse events. While prior studies have demonstrated the effectiveness of these types of interventions, there has been limited research into how the inclusion of psychological interventions as part of the programme impacts parent-reported and patient-reported quality of life. Materials and methods: Patients between the ages of 7 and 24 years with CHD completed a cardiac rehabilitation programme that followed a flexible structure of four in person-visits with various multidisciplinary team members, including paediatric psychologists. Changes in scores from the earliest to the latest session were assessed regarding exercise capacity, patient functioning (social, emotional, school, psychosocial), patient general and cardiac-related quality of life, patient self-concept, and patient behavioural/emotional problems. Results: From their baseline to final session, patients exhibited significant improvement in exercise capacity (p = 0.00009). Parents reported improvement in the patient's emotional functioning, social functioning, school functioning, psychosocial functioning, cognitive functioning, communication, and overall quality of life. While patients did not report improvement in these above areas, they did report perceived improvement in certain aspects of cardiac-related quality of life and self-concept. Discussion: This paediatric cardiac rehabilitation programme, which included regular consultations with paediatric psychologists, was associated with divergent perceptions by parents and patients on improvement related to quality of life and other aspects of functioning despite improvement in exercise capacity. Further investigation is recommended to identify underlying factors associated with the differing perceptions of parents and patients.